2018
DOI: 10.1177/1362168818767182
|View full text |Cite
|
Sign up to set email alerts
|

Pronunciation in foreign language classrooms: Instructors’ training, classroom practices, and beliefs

Abstract: The goal of this work was to explore the training, classroom practices, and beliefs related to pronunciation of instructors of languages other than English. While several investigations of this type have been conducted in English as a second/foreign language contexts, very little is known about the beliefs and practices of teachers of languages other than English. It is unknown whether recent shifts to focusing on intelligibility, as advocated by some pronunciation scholars, are borne out in foreign language c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 39 publications
4
40
0
4
Order By: Relevance
“…Much of the research on the amount and type of pronunciation instruction has come from surveys of instructors. Studies have shown that a majority of respondents who taught ESL (Foote et al, ); EFL (Buss, ); and French, German, or Spanish introductory language courses in the United States (Huensch, ) reported that they thought such instruction was important and that they addressed pronunciation in their lessons, although they devoted little instructional time to doing so. For example, Foote et al (2011, p. 11) calculated the average amount of class time spent on pronunciation to be 6%.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Much of the research on the amount and type of pronunciation instruction has come from surveys of instructors. Studies have shown that a majority of respondents who taught ESL (Foote et al, ); EFL (Buss, ); and French, German, or Spanish introductory language courses in the United States (Huensch, ) reported that they thought such instruction was important and that they addressed pronunciation in their lessons, although they devoted little instructional time to doing so. For example, Foote et al (2011, p. 11) calculated the average amount of class time spent on pronunciation to be 6%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding segmentals and suprasegmentals, in a survey of ESL instructors in Canada, Foote et al () reported a growing awareness of the importance of suprasegmental instruction for intelligibility in English; however, the observation data in Foote et al () indicated that 100% of pronunciation teaching episodes were focused on segmental as opposed to suprasegmental targets (p. 188). In Huensch (), instructors of French, German, and Spanish reported that a majority of the most serious pronunciation problems for their students were segmental, followed by spelling‐based and crosslinguistic influences, with suprasegmentals mentioned least often. It remains unclear which targets are actually focused on in practice in foreign language classes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…https://ojs.unm.ac.id/eralingua PENDAHULUAN Penelitian yang fokus mengkaji pengembangan bahan ajar bahasa asing telah banyak dilakukan oleh peneliti-peneliti sebelumnya (Koda & Yamashita, 2018;Menke & Paesani, 2019;Isik, 2018;Huensch, 2018;Han, 2018). Penelitian tersebut menggunakan pendekatan yang bervariasi dalam mengembangkan bahan ajar baik itu pendekatan integrated learning, multiliteracies framework, Task-Based Learning, dan beberapa pendekatan lainnya.…”
unclassified